Building social intelligence scale and applied to a sample at the Deprived and non-Deprived students from their parents at the Secondary stage - طالب حسين ناصر جيهان عبد حداد (College of Education for Women, 2019)
The current research aims to : •know the level of social intelligence of the sample as a whole . . •taraf statistically significant differences in social intelligence between disadvantaged and non-disadvantaged peers . To achieve these objectives, the selected sample of Talbhalmrahlh medium and specifically students of the second grade average, were chosen randomly stratified's (360) students included sex (male, female) and (deprived of the Father and the non-deprived) for the academic year (2013-2014) for the province of Baghdad on both sides (Rusafa-Karkh ( As applied to them measurements of social intelligence, which is prepared by the researcher, having achieved _khasaúsma of psychometric (valid and reliable .( When analyzing the data were used statistical methods, both when extracting multiple psychometric properties, crashes or achieve the objectives of the research, including (Pearson correlation coefficient, and the equation Alvakronbach and samples t-test for one sample and samples t-test for two independent samples The researcher found the following results : .•eetmta the sample of students from the middle school social intelligently .•The existence of statistically significant differences in social intelligence among adolescents deprived of their parents and their peers who live with their parents, and in favor of the nondeprived parents . In light of the findings of the researcher made a number of recommendations and suggestions.